Analisis Kausalitas Migrasi, Keanekaragaman dan Pertumbuhan Ekonomi di Indonesia - Della Marsel Feni; Ariusni Ariusni (Universitas Negeri Padang, 2020)
This research aims to determine whether there is a causal relationship between migration,diversity and economic growth in Indonesia. The data used are secondary data in the form of panels in 2000 and 2010, with the techniques of collection data in the form of documentation and study of literature obtained from relevant institutions and agencies. The variables use are migration, diversity, and economic growth. The research method used is Granger Causality Tests. The result show that (1) there is no causal relationship between migration and economic growth, but there is a one-way relathionship that is migration affects economic growth. (2) there is no causality or one-way relationship between diversity and economic growth. (3) there is no causality between migration and diversity